Peran Kepercayaan Diri terhadap Prestasi Belajar Matematika Siswa - Intan Vandini (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2015)
In essence, education is vital to live a social life, as well as for the development and  progress of a nation. Education also has a great influence on changing one's way of life. Since we are born we have started to get an education, especially of the family. Many parties agree that the family is the first school for students. Education does not stand by itself, a lot of factors that affect the process of education. One of them in carrying out the necessary education and learning. Teaching and learning process greatly assist learners to gain useful knowledge. In undergoing the process of teaching and learning in schools there are many fields of science, one of which is math. Mathematics is a science that its use in various fields of science or in terms of human life. In improving the learning achievement of students is confidence. This confidence must be owned by each learner. n fact, possessed the confidence of each learner is still relatively low. This is evident from the lack of a sense of confidence when working on math problems or the time to come forward to do the problems on the board. The students are still often see his answer only to can good learning achievement. Keywords: Education, self-confidence, set, math achievement.